Effects of Various Photoperiods and Specific Wavelengths on Retinal Changes and Oxidative Stress in the Conch Tegula rustica - Jin Ah Song; Heung-Sik Park; Yun-Hwan Jung; Dong Mun Choi; Cheol Young Choi; Dae-Won Lee (Fishes, 2024)
To improve aquaculture practices and husbandry of a variety of gastropods, including small conch species, it is necessary to study the physiological and endocrinological responses of nocturnal conches to light exposure. In this study, we investigated the effect of the light environment on Tegula rustica by exposing it to contrasting light conditions and observing histological changes in the retina and oxidative stress according to photoperiod and light wavelength. We confirmed that the pigment layer was significantly thicker in the group irradiated with light for 24 h (LL), but that its thickness did not differ significantly with light wavelength. Additionally, light wavelength changes did not cause a significant change in H2O2 concentration until 5 days after the change in the light environment. However, a significantly higher H2O2 concentration was observed in the LL test group on the eighth day compared with the other experimental groups. And a significantly higher total antioxidant capacity and malondialdehyde (MDA) were observed in the LL group on the third day compared with the other experimental groups. Our results indicate that the light environment affects the reaction of conches and that continuous light has a stronger effect on the thickness of the pigment layer than the light wavelength. In addition, continuous light irradiation induces excessive ROS and causes oxidative stress. These results can also be provided as basic data for husbandry when aquaculturing gastropods.